Advancements in utilizing exosomes for cancer therapy through drug delivery systems: recent developments - MohammadHossein Karami; Majid Abdouss (Nanomedicine Journal, 2025)
Researchers have successfully developed and validated diverse loading strategies, utilizing both endogenous and exogenous approaches, in laboratory and animal models, showcasing their effectiveness in advancing molecular biology research. Extracellular vesicles have advantages over synthetic carriers in disease management and therapeutics. However, their clinical application is hindered by challenges such as limited specificity, low production yield, storage stability, and targeting capability. Addressing these challenges and exploring exosome engineering techniques is crucial. Cell-derived exosomes can serve as carriers for therapeutic molecules, enabling targeted drug delivery. Understanding exosome formation and developing efficient engineering methods are essential for advancing clinical therapeutic strategies. Exosomes offer a unique approach to targeted drug delivery through intercellular communication. These natural liposomes carry endogenous biomolecules, ensuring biocompatibility and allowing for cargo loading. Genetic or chemical modifications can improve targeting and drug loading capabilities. Importantly, exosomes have weak interactions with serum proteins, extending the lifespan of the cargo. By combining the capabilities of artificial nanocarriers and intercellular signaling, exosomes provide new and reliable strategies for drug administration and medical interventions. This review examines diverse exosome types, preparation methodologies, cargo encapsulation, and their efficacy in delivering therapeutic agents across different diseases. It also highlights global companies involved in the development and testing of exosome-based therapies.